Organisational Culture and Transformational Leadership Style: Impact on Employee Performance - Kamaluddin Kamaluddin; Akmal Ridwan; Nurlianti M; Munifa Munifa (Goodwood Publishing, 2026)
Purpose – This research investigates how Organizational Culture and Transformational Leadership influence Employee Performance, and whether Culture strengthens the leadership-performance relationship. Design/methodology/approach – A quantitative method was applied, using survey data from 30 respondents. Multiple regression tested direct effects; hierarchical regression analyzed moderation. Validity and reliability were confirmed via Pearson correlation and Cronbach’s Alpha. Findings – Both Organizational Culture and Transformational Leadership significantly improve Employee Performance. Culture also acts as a positive moderator, meaning its presence amplifies leadership's effect on performance. The model has strong explanatory power. Research limitations/implications – The small sample may limit generalizability. Future studies should include larger, diverse samples and longitudinal designs to better assess causality. Practical implications – Organizations should concurrently develop strong cultures and transformational leadership, as their combined effect outperforms isolated efforts. Integrated HR and leadership programs are recommended. Social implications – Fostering such environments promotes ethical leadership, fairness, and well-being at work, supporting broader social sustainability goals. Originality/value – This study offers empirical evidence on both direct and interactive roles of culture and leadership, advancing beyond simple effect models and highlighting their synergy in driving performance.